A novel spirocyclic scaffold accessed via tandem Claisen rearrangement/intramolecular oxa-Michael addition - Vepreva, Anastasia; Yanovich, Alexander; Dar’in, Dmitry; Kantin, Grigory; Bunev, Alexander; Krasavin, Mikhail (Beilstein Journal of Organic Chemistry, 2022)
A straightforward access to novel spiro[benzofuran-2,3'-pyrrolidine]-2',5'-diones based on the Rh2(esp)2-catalyzed insertion of carbenes derived from diazo arylidene succinimides (DAS) into the O–H bond of phenols is described. The initial adducts underwent a thermally promoted Claisen rearrangement followed by DABCO-catalyzed intramolecular 5-exo-trig oxa-Michael addition.
Keywords: Claisen rearrangement; diazo arylidene succinimides; intramolecular oxa-Michael addition; rhodium(II) carbene O–H insertion; spirocycles

(untitled) - Hiesinger, K.; Dar’in, D.; Proschak, E.; Krasavin, M. (J. Med. Chem., 2021)

(untitled) - Zheng, Y.; Tice, C. M.; Singh, S. B. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Zheng, Y.-J.; Tice, C. M. (Expert Opin. Drug Discovery, 2016)

(untitled) - Chupakhin, E.; Babich, O.; Prosekov, A.; Asyakina, L.; Krasavin, M. (Molecules, 2019)

(untitled) - Garthwaite, S. M.; McMahon, E. G. (Mol. Cell. Endocrinol., 2004)

(untitled) - Loane, C.; Politis, M. (Brain Res., 2012)

(untitled) - Ono, M.; Takamura, E.; Shinozaki, K.; Tsumura, T.; Hamano, T.; Yagi, Y.; Tsubota, K. (Am. J. Ophthalmol., 2004)

(untitled) - van Epen, J. H. (Psychiatr., Neurol., Neurochir., 1970)

Analogue-based Drug Discovery - Fischer, J.; Robin, G. C. (Wiley-VCH, 2006)

(untitled) - Ammon, E.; Villinger, A.; Ehlers, P.; Langer, P. (Synlett, 2022)

(untitled) - Iaroshenko, V. O.; Dudkin, S.; Sosnovskikh, V. Ya.; Villinger, A.; Langer, P. (Synthesis, 2013)

(untitled) - Attanasi, O. A.; Favi, G.; Giorgi, G.; Mantellini, F.; Karapetyan, V.; Langer, P. (Tetrahedron, 2009)

(untitled) - Rasool, N.; Rashid, M. A.; Adeel, M.; Görls, H.; Langer, P. (Tetrahedron Lett., 2008)

(untitled) - Rasool, N.; Rashid, M. A.; Reinke, H.; Fischer, C.; Langer, P. (Tetrahedron, 2008)

(untitled) - Vepreva, A.; Kantin, G.; Krasavin, M.; Dar’in, D. (Synthesis, 2022)

(untitled) - Vepreva, A.; Bunev, A. S.; Kudinov, A. Yu.; Kantin, G.; Krasavin, M.; Dar’in, D. (Beilstein J. Org. Chem., 2022)